Associação entre aleitamento infantil, más oclusões e padrão facial na dentadura decídua: estudo epidemiológico em zonas rural e urbana do estado de aragua, venezuela - Bello, Marisela González de (2010)
The aim of this research was to evaluate the associations between infant feeding method and prevalences of malocclusions and facial patterns in primary dentition, in rural and urban zones of the State of Aragua, Venezuela. The infant feeding method was investigated by questionnaires. Four dentists performed occlusal examinations and an orthodontist took facial photographies of the profile and front view. The sample consisted of 817 children (403 from the rural and 414 from the urban zone), of both genders (418 girls and 399 boys), aged 3-6 years (mean: 4.59 ± 0.60). The children were distributed into the following groups: A1 - never breastfed; A2 - breastfed for less than 3 months; A3 - breastfeeding interrupted between 3 and 5 months; A4 - breastfeeding interrupted between 6 and 9 months; A5 - breastfed for longer than 9 months; M1 - never bottle-fed; M2 - bottle-fed up to 2 years; M3 - bottle-feeding interrupted between 3 and 4 years and M4 - bottle-fed up to 5 years. Logistic regression models were adjusted to analyze the effect of infant feeding and residential zone on the studied characteristics. Malocclusions were more prevalent in the rural zone: anterior open bite (9.4% versus 8.2%) and posterior crossbite (6.2% versus 3.1%). The opposite was found for increased overjet (30.5% versus 39.1%). Pattern II profile was the most prevalent in the rural (56.3%) and urban (62.6%) zones, followed by Pattern I (rural: 39.7%; urban: 32.6%). The Mesofacial type was the most prevalent in the rural (52.1%) and urban (44.4%) zones. The Dolichofacial type was observed in approximately one third of the children. The chances (RC) of presenting increased overjet would be greater for the set A1+A2 in comparison with group A5 (RC = 2.2; p = 0.003), as well as for group M2 (RC = 2.8; p = 0.019) and the set M3+M4 (RC = 4.8; p < 0.001), when compared with M1. For anterior open bite, the chances would be greater for the set A1+A2 in comparison with A4 (RC = 2.7; p = 0.011) and A5 (RC = 4.2; p = 0.001). The chances of diagnosing posterior crossbite would be significantly higher in the rural zone. Groups A4 (RC = 2.7; p = 0.002) and A5 (RC = 3.8; p < 0.001) would demonstrate higher chances of presenting Pattern I in relation to Pattern II, when compared with set A1+A2. Group M1 would have a greater chance (RC = 2.6; p = 0.001) of presenting Pattern I in relation to Pattern II, when compared with set M3+M4. The chances of presenting Mesofacial type in relation to the Dolichofacial would be greater for groups A4 (RC = 3.1; p < 0.001) and A5 (RC = 2.8; p < 0.001), when compared with set A1+A2. Breastfeeding beyond the age of 9 months was significantly associated with lower prevalences of increased overjet, anterior open bite, Pattern II profile and Dolichofacial type. Bottle-feeding had significant association with the highest prevalences of increased overjet and Pattern II profile.